The Dynamics of Life After Divorce: Can Women Survive? - Kiranantika, Anggaunita; Jazilah, Nikmatul (International Journal of Psychosocial Rehabilitation, 2020)
A family is a group of people united by blood, marriage, or adoption and living under the same roof. Each member of the family has his or her rights, responsibilities, and roles. In a community, such as in Malang City, Indonesia,s many women become heads of the household due to divorce in their marriage. The role of women today is no longer related solely to the role of wives or homemakers who only manage the households, but they also play a role in the public sectors to meet the needs of their families. This research was conducted qualitatively with an existentialism feminist approach. The location of the research was in Malang City, East Java, Indonesia and the research subjects were 13 women who were divorced and had children. The research employed purposive sampling and data reduction as well as resource triangulation. The results of this research were: a) explaining the meaning of divorced Female Heads of Household to their children was a challenging task, especially for women who were unemployed when they were still single or only homemakers when they were still married. b) the Female Heads of Household found it difficult to find a job after being faced with a new role as a head of household and at the same time being a homemaker who manages the households. Consequently, they often choose to owe money and rely on family help to meet their family's needs.